Trends in U.S. MD–PhD Program Matriculant Diversity by Sex and Race/Ethnicity. (17th May 2022) - Martinez-Strengel, Angela; Samuels, Elizabeth A.; Cross, Jeremiah; Cramer, Laura D.; Desai, Mayur M.; Gotian, Ruth; Gross, Cary P.; Latimore, Darin; Cavazos, Jose E.; Boatright, Dowin
Abstract : Purpose: To examine demographic characteristics of matriculants to U.S. MD–PhD programs by sex and race/ethnicity from academic years (AYs) 2009–2018 and explore the relationships between trends in the percentage of female and underrepresented minority (URM) matriculants to programs with and without Medical Scientist Training Program (MSTP) funding. Method: Linear regression and time trend analysis of the absolute percentage of matriculants into all U.S. MD–PhD programs was performed for self-reported sex and race/ethnicity, using Association of American Medical Colleges data for AYs 2009–2018, including an interaction for MSTP funding status (yes/no) and year. Linear regression of the percentage of programs matriculating no female or no URM students between AYs 2009 and 2018 was performed, focusing on programs in the top 3 quartiles by size (i.e., those matriculating 4 or more students per year). Results: Between AYs 2009 and 2018, the percentage of matriculants to all MD–PhD programs who were female (38.0%–46.0%, 1.05%/year, P = .002) or URM (9.8%–16.7%, 0.77%/year, P < .001) increased. The annual percentage gains of URM matriculants were greater at MSTP-funded programs compared with non-MSTP-funded programs (0.50%/year, P = .046). Moreover, among MD–PhD programs in the top 3 quartiles by size, the percentage of programs with no female matriculants decreased by 0.40% per year ( P = .02) from 4.6% in 2009 to 1.6% in 2018, and the percentage of programs with no URM matriculants decreased by 3.41% per year ( P < .001) from 49% in 2009 to 22% in 2018. Conclusions: A consistent and sustained increase in the percentage of female and URM matriculants to MD–PhD programs from AYs 2009–2018 was observed, but the annual increases in the percentages across groups were small, and the demographics of the MD–PhD workforce still do not reflect the diversity of the U.S. general population.